Faktor-Faktor Yang Mempengaruhi Kelemahan Pengendalian Intern Pemerintah Daerah(Studi Kasus Pemerintah Daerah Se-Eks Karesidenan Surakarta) - PRIYADI, ARIS, Zulfikar, SE, M.Si (2017)
Internal controls have a very important role for an organization, including local governments. The purpose of this study was to determine the effect of economic growth, size, revenue (PAD), and the complexity of the weakness of internal control of local governments. This research uses descriptive conducted on local government district / city in the former Surakarta residency in the period 2011 - 2015. The population in this study were seven local government districts and cities in the former Surakarta residency. Samples are financial highlights seven local government districts and cities in the former Surakarta residency period 2011-2015. The sample was taken by purposive sampling technique. Data were analyzed using classical assumption test and multiple regression analysis, t test, F test, and test the coefficient of determination. The results showed that: (1) economic growth affect the internal control weaknesses District Government / City Ex-Surakarta 2011-2015. T test results received on a significance level of 5%. This means that economic growth has implications for increasing internal control weaknesses; (2) The size of the local government (size) does not affect the internal control weaknesses District Government / City Ex-Surakarta 2011-2015. T-test was rejected at the 5% significance level. This means that the size is not implicated in the increasing weakness of internal control; (3) Regional Income positive effect on internal control weaknesses District Government / City Ex-Surakarta 2011-2015. T test results received on a significance level of 5%. That is the level of PAD have an impact on local government internal control weaknesses; (4) The complexity does not affect the internal control weaknesses District Government / City Ex-Surakarta 2011- 2015. T test results declined 5% significance level. Complexity is not implicated in the increasing weakness of internal control.